ФРАНЦУЗ ВА ЎЗБЕК ТИЛЛАРИДА ҚЎШМА СЎЗЛАР ВА УЛАРНИНГ ЎРГАНИЛИШИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to the use of compound words in the French and Uzbek languages, the formation of compound words and their place and importance in the text.
Keywords: linguistics, participle, possessor, component, word groups.